Westonci.ca is the best place to get answers to your questions, provided by a community of experienced and knowledgeable experts. Experience the ease of finding reliable answers to your questions from a vast community of knowledgeable experts. Join our platform to connect with experts ready to provide precise answers to your questions in different areas.
Sagot :
To determine the truth value of the compound statement [tex]\(\neg[(\neg p \wedge q) \vee r]\)[/tex], we follow these steps:
1. Identify the truth values for [tex]\(p\)[/tex], [tex]\(q\)[/tex], and [tex]\(r\)[/tex]:
- [tex]\(p\)[/tex] is true ([tex]\(p = \text{True}\)[/tex]).
- [tex]\(q\)[/tex] is false ([tex]\(q = \text{False}\)[/tex]).
- [tex]\(r\)[/tex] is false ([tex]\(r = \text{False}\)[/tex]).
2. Calculate [tex]\(\neg p\)[/tex]:
[tex]\[ \neg p = \neg (\text{True}) = \text{False} \][/tex]
3. Calculate [tex]\((\neg p \wedge q)\)[/tex]:
[tex]\[ (\neg p \wedge q) = (\text{False} \wedge \text{False}) = \text{False} \][/tex]
4. Calculate [tex]\((\neg p \wedge q) \vee r\)[/tex]:
[tex]\[ (\neg p \wedge q) \vee r = (\text{False} \vee \text{False}) = \text{False} \][/tex]
5. Calculate [tex]\(\neg[(\neg p \wedge q) \vee r]\)[/tex]:
[tex]\[ \neg[(\neg p \wedge q) \vee r] = \neg (\text{False}) = \text{True} \][/tex]
Therefore, the truth value of the compound statement [tex]\(\neg[(\neg p \wedge q) \vee r]\)[/tex] is [tex]\(\text{True}\)[/tex].
1. Identify the truth values for [tex]\(p\)[/tex], [tex]\(q\)[/tex], and [tex]\(r\)[/tex]:
- [tex]\(p\)[/tex] is true ([tex]\(p = \text{True}\)[/tex]).
- [tex]\(q\)[/tex] is false ([tex]\(q = \text{False}\)[/tex]).
- [tex]\(r\)[/tex] is false ([tex]\(r = \text{False}\)[/tex]).
2. Calculate [tex]\(\neg p\)[/tex]:
[tex]\[ \neg p = \neg (\text{True}) = \text{False} \][/tex]
3. Calculate [tex]\((\neg p \wedge q)\)[/tex]:
[tex]\[ (\neg p \wedge q) = (\text{False} \wedge \text{False}) = \text{False} \][/tex]
4. Calculate [tex]\((\neg p \wedge q) \vee r\)[/tex]:
[tex]\[ (\neg p \wedge q) \vee r = (\text{False} \vee \text{False}) = \text{False} \][/tex]
5. Calculate [tex]\(\neg[(\neg p \wedge q) \vee r]\)[/tex]:
[tex]\[ \neg[(\neg p \wedge q) \vee r] = \neg (\text{False}) = \text{True} \][/tex]
Therefore, the truth value of the compound statement [tex]\(\neg[(\neg p \wedge q) \vee r]\)[/tex] is [tex]\(\text{True}\)[/tex].
We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. Get the answers you need at Westonci.ca. Stay informed with our latest expert advice.